Breast arterial calcification association with coronary artery calcium scoring and implications for cardiovascular risk assessment in women. Issue 9 (26th April 2017) - Ryan, Angela J.; Choi, Andrew D.; Choi, Brian G.; Lewis, Jannet F.
Abstract : Breast arterial calcification (BAC) is a type of medial artery calcification that can be seen incidentally on mammography. Studies have suggested association of BAC with cardiovascular risk factors, coronary artery disease (CAD), and cardiovascular morbidity and mortality. Recently published studies have also suggested a modest correlation of BAC with coronary artery calcium (CAC) scoring. Roughly 40 million mammograms are already performed annually in the United States with overlap in patients that undergo CAD screening via CAC scoring. Thus, identification of cardiovascular risk by demonstrating an association between BAC and CAC may enable an instrumental sex‐specific methodology to identify asymptomatic women at risk for CAD. The purpose of this article is to review the current state of the literature for BAC and its association with CAC, to review contemporary breast cancer screening guidelines, and to discuss the clinical implications of these findings.